Effect of Endurance training with garlic supplement on serum glutathione and some cellular damage markers in non-active men in response to one session of exhaustive exercise - رضا غنیمتی; خسرو ابراهیم; بهنام سالاری; سمیرا غلامیان; لاله حقوقی راد (Shahid Beheshti University, 2013)
Effect of Endurance training with garlic supplement on serum glutathione and some cellular damage markers in non-active men in response to one session of exhaustive exercise Purpose: The purpose of this study was to investigate the effect of endurance training with garlic supplement on serum glutathione and lactate dehydrogenase and creatine kinase in non-active men in after one session of exhaustive exercise. Methods: In this study thirty two non smoker men with mean age of (25.7±2.1 yr) participated voluntarily and divided randomly into four groups; (placebo, garlic, placebo-training, garlic- training). During one month, all groups took 500 mg٫day garlic and placebo. The two training group participated in a training protocol (running on treadmill with intensity of 65-75 HRmax for 30-45 min). All four groups participated in one session of exhaustive exercise considering Bruce protocol before and 48 hr after last training session and supplement consumption. Four blood sample ware collected from subjects before and after exhaustive exercise. Result: Statistical analysis revealed no significant difference in resting glutathione between four groups. The serum glutathione concentration in response to exhaustive exercise showed significant decrease in three group compare to placebo group (P-0.001). The resting LDH level (P-0.022), CK (P=0.001) in garlic, placebo-exercise and garlic-exercise group compare to control group showed significant decrease. Lactate dehydrogenase and creatine kinase in response to one session of exhaustive exercise was not influenced by endurance training and the use of garlic. Conclusion: Endurance training and garlic can by increasing the activity of glutathione anti-oxidative system be reduce resting cellular damage in non-active men.